A dual-emission color-adjustable composite glass-ceramic and its preparation method and application
By using dual-emission tunable color composite glass ceramics in optical anti-counterfeiting materials, and using their linear photoluminescence changes under different ultraviolet light excitation, the problem that the single mode of existing optical anti-counterfeiting materials is easily identified or forged, and the secondary encryption of information and efficient anti-counterfeiting are achieved.
Patent Information
- Application Number
- CN202310367294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The single mode of existing optical anti-counterfeiting materials is easily identified or forged, lacks response to different excitation lights, and it is difficult to achieve secondary encryption of information and efficient anti-counterfeiting.
Dual emission tunable color composite glass ceramics are used, which have linear photoluminescence changes under different ultraviolet light excitation, and the reading and secondary encryption of anti-counterfeiting information are realized through variable excitation luminescence. The material consists of a borosilicate glass matrix, ZnS powder and halide ionic inorganic salts, and is prepared by a one-step melt-cold quenching method.
The adjustability of light response under different excitation lights is achieved, the anti-counterfeiting performance and information encryption capabilities of the material are enhanced, and the imitation cost is reduced.
Smart Images

Figure CN116282927B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of luminescent materials, and in particular to a dual-emission color-adjustable composite glass ceramic and a preparation method and application thereof. Background Art
[0002] At present, in the field of anti-counterfeiting, visible optical anti-counterfeiting is a direction that has received much attention. Due to its visual readability, it is more convenient and faster than other anti-counterfeiting technologies (such as instrument decoding anti-counterfeiting), and has huge advantages in protecting information security and practicality. However, despite the great advantages of optical anti-counterfeiting, its single anti-counterfeiting mode makes it easy to be identified or forged. Therefore, it is crucial to develop optical anti-counterfeiting materials that have different responses to light excitation. This light response that changes according to the excitation light means that the color coordinates corresponding to the light response of the material can be used to achieve secondary encryption and reading of information during reading. In addition, due to the special nature of the material, the cost of counterfeiting is relatively high, so it is particularly important to develop an advanced optical anti-counterfeiting material to achieve information encryption and anti-counterfeiting. Summary of the invention
[0003] To solve the above problems, the dual-emission color-adjustable composite glass-ceramic provided by the present invention has linear photoluminescence changes under different ultraviolet light excitations. The anti-counterfeiting information can be read and re-encrypted by utilizing this variable excitation photoluminescence, which is of great significance in the field of anti-counterfeiting.
[0004] Another object of the present invention is to provide a preparation method and application of the above-mentioned dual-emission color-adjustable composite glass-ceramics.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0006] A dual-emission color-adjustable composite glass ceramic and a preparation method thereof, characterized in that the raw materials for preparing the composite glass ceramic include a borosilicate glass matrix, ZnS powder and a halogen ion inorganic salt, the borosilicate glass matrix is a sodium oxide-zinc oxide-boric acid-silicon dioxide glass system; the halogen ions exist in the form of halogen ion inorganic salts.
[0007] Preferably, the preparation process of the composite glass-ceramic comprises:
[0008] S1: The borosilicate glass matrix, ZnS powder, and halogen ion inorganic salt are accurately weighed and placed in a purple agate mortar to grind and mix evenly to obtain a mixture, and the mixture is placed in a box furnace for pre-drying;
[0009] S2: placing the pre-dried mixture into a high-temperature furnace for high-temperature melting treatment, then casting the melt into a mold for forming and keeping it warm, and then cooling it to room temperature to obtain the dual-emission color-adjustable composite glass-ceramic.
[0010] Furthermore, the borosilicate glass matrix has a ratio of 10 mol% to 20 mol% sodium oxide, 10 mol% to 30 mol% zinc oxide, 40 mol% to 60 mol% boric acid, and 10 mol% to 30 mol% silicon dioxide.
[0011] Furthermore, the ZnS powder is added in an amount of 5 mol% to 30 mol% of the borosilicate glass matrix, and the crystal configuration of the ZnS is one or more of a wurtzite structure and a zinc blende structure.
[0012] Preferably, the halogen ion inorganic salt exists in the form of AB; A: one or more of Li, Na, K; B: one or more of Cl, Br, I, F.
[0013] Furthermore, the amount of the halogen ion inorganic salt added is 1 mol% to 40 mol% of the borosilicate glass matrix.
[0014] Preferably, the step S1 is specifically that the pre-drying treatment temperature is 100° C. to 150° C. and the pre-drying treatment time is 10 min to 60 min.
[0015] Preferably, the step S2 is specifically as follows: the high-temperature melting temperature is 900°C to 1350°C, the melting time is 5min to 60min, the molten body is cast in a mold with a preheating temperature of 200°C to 300°C, and the heat preservation is 0.5h to 3h. The high-temperature furnace includes but is not limited to a pit furnace, a muffle furnace or a box furnace, and then naturally cooled.
[0016] According to another aspect of the present application, a variable excitation optical anti-counterfeiting application is provided, comprising the above-mentioned composite glass or a composite glass ceramic prepared by the above-mentioned preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The glass matrix of the dual-emission color-adjustable composite glass-ceramic provided by the present invention is a sodium oxide-zinc oxide-boric acid-silicon dioxide glass system, which has stable physical and chemical properties and can effectively improve mechanical properties; the preparation method of the composite glass-ceramic is a one-step melting-cold quenching method, which is simple and low-cost. After being excited by ultraviolet light, the dual-emission color-adjustable composite glass-ceramic provided by the present invention produces a double-peak broadband fluorescence emission at 450nm and 505nm. The doping of halogen ions changes the intrinsic emission center of ZnS, and the difference in the light response between defects and intrinsic emission centers is used to achieve variable photochromism that changes with the excitation wavelength, so that it can be applied to the field of anti-counterfeiting.
[0019] (2) The preparation method provided by the present invention has no special requirements for equipment, is low in cost, safe and environmentally friendly, and can be widely promoted for production.
[0020] (3) The dual-emission color-adjustable composite glass-ceramic provided by the present invention may become a practical application for anti-counterfeiting and deep encryption. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a fluorescence emission spectrum of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 of the present invention;
[0022] Figure 2 This is an XRD characterization diagram of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 of the present invention.
[0023] Figure 3 This is a fluorescence emission spectrum of the dual-emission color-adjustable composite glass-ceramic prepared in Example 2 of the present invention;
[0024] Figure 4 This is a fluorescence emission spectrum of the dual-emission color-adjustable composite glass-ceramic prepared in Example 3 of the present invention;
[0025] Figure 5 This is a color coordinate change diagram of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 of the present invention at an excitation wavelength of 280-320 nm.
[0026] Figure 6 This is a fitting diagram of the fluorescence intensity ratio of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 of the present invention at an excitation wavelength of 280-320 nm.
[0027] Figure 7 This is a color coordinate change diagram of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 of the present invention at an excitation wavelength of 340-380 nm.
[0028] Figure 8 This is a fitting diagram of the fluorescence intensity ratio of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 of the present invention at an excitation wavelength of 340-380 nm.
[0029] Fig. 9 This is a schematic diagram of the anti-counterfeiting application of the dual-emission color-adjustable composite glass-ceramic prepared in Application Example 1 of the present invention under the irradiation of sunlight, 280nm ultraviolet light, and 380nm ultraviolet light. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the scope of the present invention.
[0031] Embodiment 1:
[0032] The present embodiment provides a dual-emission color-adjustable composite glass-ceramic. Analytically pure sodium oxide, zinc oxide, boric acid, silicon dioxide, ZnS, and NaBr are accurately weighed according to the matrix glass raw materials of 20 mol% sodium oxide, 15 mol% zinc oxide, 45 mol% boric acid, 20 mol% silicon dioxide, 10 mol% ZnS, and 10 mol% NaBr, and placed in an agate mortar. After being evenly ground in the agate mortar, the mixture is placed in a corundum crucible, transferred to a box furnace at 100°C and dried for 20 minutes, and then placed in a muffle furnace at 1050°C for high-temperature melting for 10 minutes. Then, the glass melt is taken out and quickly cast into a mold with a preheating temperature of 250°C for forming, kept warm for 1.5 hours, and then naturally cooled to obtain a Br-doped dual-emission color-adjustable composite glass-ceramic.
[0033] Embodiment 2:
[0034] The present embodiment provides a dual-emission color-adjustable composite glass-ceramic. Analytically pure sodium oxide, zinc oxide, boric acid, silicon dioxide, ZnS, and KCl are accurately weighed according to the matrix glass raw materials of 20 mol% sodium oxide, 15 mol% zinc oxide, 45 mol% boric acid, 20 mol% silicon dioxide, 10 mol% ZnS, and 10 mol% KCl, and placed in an agate mortar. After being evenly ground in the agate mortar, the mixture is placed in a corundum crucible, transferred to a box furnace at 150°C and dried for 10 minutes, and then placed in a muffle furnace at 1000°C for high-temperature melting for 20 minutes. Then, the glass melt is taken out and quickly cast into a mold with a preheating temperature of 200°C for forming, kept warm for 1 hour, and then naturally cooled to obtain the Cl-doped dual-emission color-adjustable ZnS composite glass-ceramic.
[0035] Embodiment three:
[0036] The present embodiment provides a dual-emission color-adjustable composite glass-ceramic. Analytically pure sodium oxide, zinc oxide, boric acid, silicon dioxide, ZnS, and LiI are accurately weighed according to the matrix glass raw materials of 10 mol% sodium oxide, 25 mol% zinc oxide, 50 mol% boric acid, 15 mol% silicon dioxide, 15 wt% ZnS, and 10 wt% LiI, and placed in an agate mortar. After being evenly ground in the agate mortar, the mixture is placed in a corundum crucible, transferred to a box furnace at 100° C. and dried for 20 minutes, and then placed in a muffle furnace at 1100° C. and melted for 12 minutes. Then, the glass melt is taken out and quickly cast into a mold with a preheating temperature of 300° C. to form, kept warm for 2 hours, and then naturally cooled to obtain an I-doped dual-emission color-adjustable composite glass-ceramic.
[0037] Application Example 1:
[0038] This embodiment provides a practical application of a dual-emission color-adjustable composite glass-ceramic. The composite glass-ceramic prepared in Example 1 is ground into powder or prepared into a slurry, and then the powder or slurry is injected into a pre-prepared mold pattern to complete the required information encryption.
[0039] Figure 1 The fluorescence emission spectrum of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1. Under 365nm excitation, the Br-doped dual-emission color-adjustable composite glass-ceramic prepared in Example 1 has the optical characteristics of double-peak emission at 450nm and 505nm, and the emission band covers the spectral region from 410nm to 650nm.
[0040] Figure 2 The XRD characterization diagram of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1. The test was performed using an Ultima IV high-resolution diffractometer produced by Rigaku Corporation of Japan. The XRD curve in Example 1 shows a standard amorphous structure of glass, indicating that the prepared composite glass has a characteristic glass phase. In addition, compared with the standard PDF card of wurtzite, the basic diffraction peak positions correspond one to one, indicating that wurtzite ZnS exists in the composite glass-ceramic.
[0041] Figure 3 This is the fluorescence emission spectrum of the dual-emission color-adjustable composite glass-ceramic prepared in Example 2. Under 365nm excitation, the Cl-doped dual-emission color-adjustable composite glass-ceramic also has the optical characteristics of double-peak emission at 450nm and 505nm, but the intensity of its green light emission is higher than that of the Br-doped dual-emission color-adjustable composite glass-ceramic, and the emission band covers the spectral region from 410nm to 650nm.
[0042] Figure 4 This is the fluorescence emission spectrum of the dual-emission color-adjustable composite glass-ceramic prepared in Example 3. Under 365nm excitation, the I-doped dual-emission color-adjustable composite glass-ceramic also has the optical characteristics of double-peak emission at 450nm and 505nm, which is similar to the luminescence of the Cl-doped dual-emission color-adjustable composite glass-ceramic prepared in Example 2. The intensity of its green light emission is strong, and the emission band covers the spectral region from 410nm to 650nm.
[0043] Figure 5 The figure is a color coordinate change diagram of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 at an excitation wavelength of 280-320nm. As can be seen from the figure, at an excitation wavelength of 280-320nm, the color coordinates of the sample prepared in Example 1 move to a bluer region as the excitation wavelength redshifts, indicating that the blue light emission is more enhanced than the green light emission.
[0044] Figure 6This is a fitting diagram of the fluorescence intensity ratio of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 at an excitation wavelength of 280-320nm. Origin was used for fitting, and the fitting formula and fitting degree are given in the figure. It can be seen from the figure that at an excitation wavelength of 280-320nm, the fluorescence intensity ratio increases linearly with Figure 5 Corresponding to the analysis, the blue light emission is enhanced in this excitation wavelength region, indicating that the dual-emission tunable color composite glass-ceramics can realize the reading of anti-counterfeiting information through fluorescence intensity within this excitation wavelength range.
[0045] Figure 7 The figure is a color coordinate change diagram of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 at an excitation wavelength of 340-380nm. As can be seen from the figure, at an excitation wavelength of 340-380nm, the color coordinates of the sample prepared in Example 1 move to a greener region as the excitation wavelength redshifts, indicating that under this wavelength change, the green light emission of the dual-emission color-adjustable composite glass-ceramic is more enhanced than the blue light emission.
[0046] Figure 8 This is a fitting diagram of the fluorescence intensity ratio of the dual-emission color-adjustable composite glass-ceramic prepared in Example 1 at an excitation wavelength of 340-380nm. Origin was used for fitting, and the fitting formula and fitting degree are given in the figure. It can be seen from the figure that at an excitation wavelength of 340-380nm, its fluorescence intensity ratio decreases nonlinearly, which is consistent with Figure 7 This corresponds to the phenomenon shown in Figure 2, indicating that the dual-emission color-tunable composite glass-ceramics can also read anti-counterfeiting information through fluorescence intensity within this excitation wavelength range.
[0047] Fig. 9 This is a schematic diagram of the anti-counterfeiting application of the dual-emission color-adjustable composite glass-ceramic prepared in Application Example 1 of the present invention under sunlight, 280nm ultraviolet light, and 380nm ultraviolet light. Under sunlight, the entire pattern appears grayish white, and no specific information can be obtained, while under 280nm ultraviolet light, the pattern shows a badge; turn off the 280nm excitation source and replace it with 380nm light excitation, then the badge required to be encrypted is still displayed, but the color of the badge changes from blue to cyan blue, which is the variable excitation color-adjustable characteristic of the composite glass-ceramic provided by the present invention, and because the color changes, it can be expanded to a secondary encryption effect identified by color or color coordinates. After the above characterization, it is shown that this material can realize the practical application of variable excitation photochromic anti-counterfeiting.
[0048] The above content is a further explanation of the present invention in combination with the preferred technical solution, and the examples described are part of the examples of the present invention, but not all of the examples. For researchers in the technical field to which the present invention belongs, simple deductions and substitutions can be made without departing from the concept, and other examples obtained without creative work are all within the scope of protection of the present invention.
Claims
1. A dual-emission color-adjustable composite glass-ceramic, characterized in that: The raw materials for preparing the composite glass ceramics include borosilicate glass matrix, ZnS powder and halogen ion inorganic salts, wherein the borosilicate glass matrix is a sodium oxide-zinc oxide-boric acid-silicon dioxide glass system, and the dual-emission color-adjustable composite glass ceramics generate double-peak fluorescence emission at 450nm and 505nm after being excited by ultraviolet light; The borosilicate glass matrix has a ratio of 10 mol% to 20 mol% sodium oxide, 10 mol% to 30 mol% zinc oxide, 40 mol% to 60 mol% boric acid, and 10 mol% to 30 mol% silicon dioxide; The ZnS powder is added in an amount of 5 mol% to 30 mol% of the borosilicate glass matrix; The halogen ion inorganic salt exists in the form of AB; A: one or more of Li, Na, K; B: one or more of Cl, Br, I, F; The amount of the halogen ion inorganic salt added is 1 mol% to 40 mol% of the borosilicate glass matrix.
2. The method for preparing a dual-emission color-adjustable composite glass-ceramic according to claim 1, characterized in that: The preparation process of composite glass ceramics includes: S1: The borosilicate glass matrix, ZnS powder, and halogen ion inorganic salt are accurately weighed and placed in a purple agate mortar to grind and mix evenly to obtain a mixture, and the mixture is placed in a box furnace for pre-drying; S2: placing the pre-dried mixture into a high-temperature furnace for high-temperature melting treatment, then casting the melt into a mold for forming and keeping it warm, and then cooling it to room temperature to obtain the dual-emission color-adjustable composite glass-ceramic.
3. The method for preparing the dual-emission color-adjustable composite glass-ceramic according to claim 2, characterized in that: The temperature of the pre-drying treatment is 100°C to 150°C; the time of the pre-drying treatment is 10min to 60min.
4. The method for preparing the dual-emission color-adjustable composite glass-ceramic according to claim 2, characterized in that: The high-temperature melting temperature is 900°C to 1350°C, the melting time is 5min to 60min, the molten body is cast in a mold preheated at 200°C to 300°C, kept warm for 0.5h to 3h, and then cooled naturally. The high-temperature furnace is a pit furnace, a muffle furnace or a box furnace.
5. Application of the dual-emission color-adjustable composite glass-ceramic according to claim 1 or the composite glass-ceramic prepared by the method for preparing the dual-emission color-adjustable composite glass-ceramic according to claims 2-4, characterized in that It is an anti-counterfeiting application of variable excitation optics.
Citation Information
Patent Citations
Full-inorganic perovskite quantum dot composite glass and preparation method thereof
CN115259663A